2018
DOI: 10.1155/2018/3758068
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio, Monocyte-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Mean Platelet Volume-to-Platelet Count Ratio as Biomarkers in Critically Ill and Injured Patients: Which Ratio to Choose to Predict Outcome and Nature of Bacteremia?

Abstract: Background Neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume-to-platelet count (MPV/PC) ratio are readily available parameters that might have discriminative power regarding outcome. The aim of our study was to assess prognostic value of these biomarkers regarding outcome in critically ill patients with secondary sepsis and/or trauma. Methods A total of 392 critically ill and injured patients, admitted to surgical ICU, were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
175
7
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 47 publications
18
175
7
10
Order By: Relevance
“…From this point forward, recent studies showed that PLR was another indicator of inflammation and can be used for predicting the prognosis of septic patients . Djordjevic et al ., compared patients who had polymicrobial and negative blood cultures in the intensive care unit and found that PLR values were lower in patients with polymicrobial blood culture . In addition, Can et al ., reported that there was a positive association between the early onset of neonatal sepsis and PLR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point forward, recent studies showed that PLR was another indicator of inflammation and can be used for predicting the prognosis of septic patients . Djordjevic et al ., compared patients who had polymicrobial and negative blood cultures in the intensive care unit and found that PLR values were lower in patients with polymicrobial blood culture . In addition, Can et al ., reported that there was a positive association between the early onset of neonatal sepsis and PLR .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Djordjevic et al, compared patients who had polymicrobial and negative blood cultures in the intensive care unit and found that PLR values were lower in patients with polymicrobial blood culture. 23 In addition, Can et al, reported that there was a positive association between the early onset of neonatal sepsis and PLR. 24 In our study, there was not a statistically significant difference between groups in terms of PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from presepsin, mean platelet volume and lactate levels were included. We demonstrated, in our previous research, that mean platelet volume was independent predictor of lethal outcome in critically ill and injured patients who developed secondary sepsis (3). Lactate levels are routinely used to assess circulatory function and tissue perfusion.…”
mentioning
confidence: 84%
“…It is evident that this life-threatening organ dysfunction, resulting from uncontrolled host response to infection, is responsible for one fifth of all deaths despite all the latest technology and newer antibiotics. Bearing in mind the importance of mortality prediction in critically ill septic patients, investigators, over the years, focused their attention to various potential biomarkers in this regard (2,3). So far, no specific biomarkers for mortality prediction in this patient population have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, MPVPCR has been reported to be high in cases such as sepsis [19] , hepatic fibrosis [20] , peritonitis and pancreatitis [21] , and this situation is reported to be associated with mortality. However, in studies performed, it was shown that MPVPCR value is more determinant than MPV value in predicting complications and cardiac mortality due to non-ST segment elevation myocardial infarction disease [22] .…”
Section: Acknowledgementmentioning
confidence: 99%